Corporate Firm Value: CEO Characteristic Factors (Gender) and CEO age - Sabilla, Akfika Rizky (Universitas Pahlawan Tuanku Tambusai, 2024)
Firm value is a very important factor for corporations that have gone public or not in maintaining the image of existing information to investors. As well as being one of the references for investors in deciding their investment actions. Thus, as an academic practitioner and also a capital market investor, this research theme is a topic of urgency in the perspective of the CEO (Gender) and the age of the CEO to be raised. The specific purpose of this study is to analyze the difference in firm value among energy sector companies listed on the Indonesia Stock Exchange, with a focus on the character of the CEO (Gender), and the age of the CEO of the corporation. The research data analysis technique uses an independent mean difference test for hypothesis testing in this study, the first thing to do first is the assumption test or the feasibility of the research data model. The results showed the first that there was no significant difference in the Company led by Female CEO and male CEO on firm value, the second result showed that there was no significant difference in the Company led by CEO less than 45 years and CEO more than 45 years of age on firm value.